Under frequency load shedding in the presence of renewable energy sources - BAADJ Mounir; GHRIBI Atallah; ARIF Salem (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electrotechnique, 2023)
The increasing use of Renewable Energy Sources (RES) in power systems has posed new challenges to maintaining stability and frequency. As the reliance on these intermittent sources of energy increases, the reliability of the power supply becomes more critical than ever. Under Frequency Load Shedding (UFLS) is an emergency control action used to restore power system balance during an imbalance. UFLS works by shedding part of the load automatically when the power system frequency falls below a predetermined threshold value. This study investigates the importance of UFLS in maintaining a reliable power supply and its effectiveness in preventing power system blackouts, particularly in the presence of RES. To evaluate the effectiveness of UFLS, we utilized the ETAP software and conducted simulations for two specific separation scenarios in three study cases using the "New England test system 39-noeud". Through our simulations, we assessed the performance of UFLS in traditional systems as well as in systems with the presence of RES. Our results showed that UFLS is an effective emergency control action that can prevent power system blackouts and restore frequency stability during imbalances. Furthermore, we analyzed the impact of RES on UFLS and developed an effective UFLS plan design that considers the amount of load in each stage and the response time of the frequency relay. These findings provide insights into the impact of RES on power system stability and demonstrate the importance of UFLS in maintaining frequency stability in power systems.
Option: Power Systems